Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.20452/pamw.4478
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care for patients with advanced lung cancer and chronic obstructive pulmonary disease – survey among Polish pulmonologists

Abstract: INTRODUCTION There is evidence that people with nonmalignant disease receive poorer end-of-life (EOL) care compared with people with cancer. OBJECTIVES The aim of the study was to assess the selected aspects of symptomatic treatment and communication between physicians and patients diagnosed with either advanced chronic obstructive pulmonary disease (COPD) or lung cancer. METHODS A questionnaire survey was conducted online among members of the Polish Respiratory Society. RESULTS Properly completed questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
(26 reference statements)
1
18
0
2
Order By: Relevance
“…Positive changes in attitudes in response to more recent knowledge about the safety and potential benefits of opioids may mean that younger clinicians are more open to using opioids. 24 However, the study which reported this finding only received an MMAT total of 1 and had limitations in terms of response rate and sampling strategy. Support from a palliative care team increased clinician willingness to prescribe opioids, particularly collaboration, communication and information sharing between palliative specialists and non-palliative specialists.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Positive changes in attitudes in response to more recent knowledge about the safety and potential benefits of opioids may mean that younger clinicians are more open to using opioids. 24 However, the study which reported this finding only received an MMAT total of 1 and had limitations in terms of response rate and sampling strategy. Support from a palliative care team increased clinician willingness to prescribe opioids, particularly collaboration, communication and information sharing between palliative specialists and non-palliative specialists.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies, one of which has a MMAT total of 5, 37 highlighted the need to improve clinician knowledge and education on opioid use for breathlessness, particularly regarding prescribing and application. 24,37,40…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent multinational and national surveys have highlighted considerable variation in treatment approaches for breathlessness between respiratory medicine (RM) and palliative care (PC) physicians [ 14 ], and in the approach to breathlessness management in malignant versus non-malignant disease [ 15 ]. Barriers to effective management include lack of clinician knowledge and experience [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%